Mycoplasma pneumoniae - the culprit for juvenile dermatomyositis in a 9-year-old girl: a case report - Anuar, Muhamad Azamin; Mohd Yusoff, Suryati; Syed Ahmad Shihabuddin Abdurrahman Alsagoff, Sharifah Aishah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Mycoplasma pneumoniae is frequently known as an “atypical bacterium” that can cause wide-ranging extrapul- monary manifestations. Here, we outline a case of a child, aged 9-year-old, who presented with profound proximal muscle weaknesses and a vague rash, associated with markedly elevated serum creatinine kinase (CK). Muscle biopsy suggested Juvenile Dermatomyositis (JDM) following an upper respiratory illness of M. pneumoniae origin. The child responded exceptionally well to a combined therapy of immunoglobulin, intravenous glucocorticoid and methotrexate.